2022
DOI: 10.1186/s12951-022-01597-1
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3 integrin-specific exosomes engineered with cyclopeptide for targeted delivery of triptolide against malignant melanoma

Abstract: Background Melanoma is the most malignant skin tumor and is difficult to cure with the alternative treatments of chemotherapy, biotherapy, and immunotherapy. Our previous study showed that triptolide (TP) exhibited powerful tumoricidal activity against melanoma. However, the clinical potential of TP is plagued by its poor aqueous solubility, short half-life, and biotoxicity. Therefore, developing an ideal vehicle to efficiently load TP and achieving targeted delivery to melanoma is a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…This system possessed superior tumor targetability and prolonged the half-life of TPL, obviously inhibiting tumor growth and extending the survival time of the mouse model of malignant melanoma via the caspase cascade and mitochondrial pathway. [102] A disease strongly associated with hepatocellular carcinoma is cirrhosis, and thus cancer-associated fibroblasts (CAFs) play an important cellular communication function in HCC. Wang et al found that miR-335-5p was downregulated in HCC cells cocultured with CAF.…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…This system possessed superior tumor targetability and prolonged the half-life of TPL, obviously inhibiting tumor growth and extending the survival time of the mouse model of malignant melanoma via the caspase cascade and mitochondrial pathway. [102] A disease strongly associated with hepatocellular carcinoma is cirrhosis, and thus cancer-associated fibroblasts (CAFs) play an important cellular communication function in HCC. Wang et al found that miR-335-5p was downregulated in HCC cells cocultured with CAF.…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…Gu et al also used triptolide as an anticancer agent but they loaded TPL into exosomes harboring a cRGD peptide, which targeted the αvβ3 integrin receptor overexpressed on melanoma cells. cRGD-Exo-TPL construct significantly inhibited melanoma growth in vivo and prolonged the half-life of TPL [ 169 ]. PEG-coated EVs were shown to deliver doxorubicin to B16-F10 murine melanoma models [ 170 ].…”
Section: Evs As Therapeutic Tools For Melanoma Treatmentmentioning
confidence: 99%
“…Furthermore, the codelivery of oxaliplatin and PGM5AS1 via sEVs improved therapeutic effects in colon cancer by reversing drug resistance . In addition to FDA-approved drugs, other small molecules, peptides, and nanoparticles coupled with sEVs were exploited to treat solid tumor malignancies. ,,, Neutrophil elastase (ELANE) and Hiltonol-loaded sEVs derived from genetically engineered MDA-MB-231 cells were able to induce immunogenic cell death in tumor organoids and orthotopic TNBC mice . This combinational drug delivery system enhanced the immunogenicity-dependent tumor regression by conventional dendric cell (DC) and CD8+ T cell responses, as compared to free Hiltonol.…”
Section: Small Evs In Cancer Drug Deliverymentioning
confidence: 99%